Numerical modelling of bipolar plate in pem fuel cells to analyse the pressure drop in various channels and development of a novel geometry of the bipolar plate. - Jayabal, Jayvassanth (Cranfield University, 2022)
This work centres on comprehending and elevating the performance of Proton Exchange Membrane (PEM) hydrogen fuel cells, with a specific emphasis on minimizing pressure drop in the bipolar plate. Fuel cell efficiency hinges upon core factors, including electrochemical reaction, temperature, and pressure management. Notably, pressure drop within the fuel cell plays a pivotal role in determining overall efficiency and power output. The study aims to tackle the pressing issue of pressure drop, primarily manifested in the bipolar plate, profoundly affecting the fuel cell's output power. Researchers have pursued ground-breaking designs to curtail pressure drop and augment power output. However, certain advanced designs pose challenges in fabrication, leading to a research gap impeding the development of efficient models. To bridge this gap, the study proposes a novel and straightforward bipolar plate design, demanding minimal external power and eliminating the need for intricate geometries. Furthermore, apart from pressure drop, fuel cell inefficiencies are compounded by obstacles like inadequate meshing and porosity integrity of the end plates. Consequently, costly platinum and gold-plated end plates are often deployed to achieve superior output performance. The research reveals that velocity variations influence pressure within existing models, furnishing valuable insights for attaining improved efficiencies in fuel cells. The work presents a comprehensive analysis of PEM fuel cells, with particular attention to the bipolar plate's design and its ramifications on pressure drop. The proposed novel geometry aims to enhance fuel cell performance while addressing challenges linked to complex designs. The research findings offer valuable recommendations for optimizing fuel cell efficiencies, thereby contributing to the advancement of clean energy technologies.
Nabavi, Sayed Ali - Associate Supervisor
Keywords: Analysis; bipolar plate; electrochemical reaction; geometry; PEM fuel cells; pressure drop